STUDENTS’ MASTERY OF SIMPLE PRESENT TENSE IN VERBAL SENTENCES: A DESCRIPTIVE STUDY AT SMP BANDAR KLIPPA - Hasanah, Pandiwi; Manugeren, M (JOURNAL OF LANGUAGE, 2025)
This study explores students’ mastery of the simple present tense in verbal sentences, emphasizing their ability to construct positive, negative, and interrogative forms. The research was conducted at SMP Bandar Klippa, located in Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, North Sumatra, during the 2023/2024 academic year. Employing a descriptive quantitative design, the study utilized an objective multiple-choice test as its primary instrument. A purposive sample of 23 students was selected from a population of 142. The findings indicate that students’ overall mastery of the simple present tense falls within the “fail” category, with a mean score of 49.56. Among the three forms assessed, Formula I (positive sentences) appeared as the most dominant, with a mean score of 0.52 or 37%. These results suggest that students struggle more with negative and interrogative sentence construction. Hence, adopting more contextualized and communicative grammar teaching methods is strongly recommended to enhance students’ grammatical accuracy and practical use of English in real-life communication.